Pengaruh Time Budget Pressure, Locus Of Conrol Dan Integritas Laporan Keuangan Terhadap Kualitas Audit Dengan Auditor Switching Sebagai Variabel Moderasi - Febria Amanda; Nera Marinda Machdar (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Every company must present quality financial reports. One way to find out quality financial reports is through a public accountant audit, which measures the level of fairness of financial reports compared to accounting standards. What happens in a country, especially in a company amidst increasingly fierce competition. Companies strive to continue making reports such as financial and annual reports which contain profiles, management discussions and corporate governance (Siagian & Machdar, 2023). External auditors or public accountants are considered independent third parties who can prevent conflicts of interest between company management and shareholders. Apart from being used by companies and shareholders, audit results are also used by stakeholders outside the company such as potential investors, creditors, the government and other related parties. All of these parties consider audit results as an important factor in decision making (Wardani et al., 2020).